Violence against women: representations of media discourse: Violence against women: representations of media discourse - Miranda, Edna Lopes; Loreto, Maria das Dores Saraiva de; Souza, Gustavo Bruno Pereira de (Argumentum, 2022)
A growing phenomenon in Brazil and across the world, violence against women goes beyond individual aspects, insofar as it affects the economic and social health of women and their children. This study analyzes the media discourse on violence against women and its consequences from an intergenerational perspective. Methodologically, research on domestic violence was carried out on the YouTube video site, using the Sociological Analysis of Discourse in interface with the Theory of Social Representations. The results showed a predominance of physical violence, with other types of domestic violence not being discussed. It also found that, even fifteen years after the creation of the Maria da Penha Law, the representations and media discourse blaming women for the violence suffered still persist, constituting a discursive "detachment" from violent family contexts.